36th AIAA/ASME/SAE/ASEE Joint Propulsion Conference and Exhibit 2000
DOI: 10.2514/6.2000-3255
|View full text |Cite
|
Sign up to set email alerts
|

Micropropulsion research at AFRL

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including t gathering and maintaining the data needed, and completing and reviewing the collection of information. Send c) collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, 2 Davis Highway, Suite 1204, Arlington, VA 22202-4302, and to the Office of Management and Budget, Paperwoi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Various attempts have been conducted to miniaturize pulsed plasma thrusters in the recent years [15,16]. A common problem in these efforts was the carbonization of the Teflon surface.…”
Section: Miniaturized Pulsed Plasmamentioning
confidence: 99%
“…Various attempts have been conducted to miniaturize pulsed plasma thrusters in the recent years [15,16]. A common problem in these efforts was the carbonization of the Teflon surface.…”
Section: Miniaturized Pulsed Plasmamentioning
confidence: 99%
“…Equation C.3 [Guman, 1975] does not apply to the regime that the micro-PPT designs (those with Ibit -5 gNs) lie in, so supplementary data [Gulczinski, 2000] was used to obtain a reasonable value for the mshot, which was then used in Equation C.4 to determine a corresponding Ibit- which equates the average power the thruster needs to consume to the average power the spacecraft must produce for it with a power transmission efficiency factor (assumed to be 0.85) and an assumed spacecraft voltage of 28 V. The following three equations for the mass of various propulsion system components comes from the same paper by Guman that is the source for Equation C. 1 [Guman, 1975] and is based on experimental data. …”
Section: 2mentioning
confidence: 99%
“…Inspection of the micro-PPT propellant surface after firing indicated signs of charring and preferential ablation near the electrodes. 8,9,13 It was identified that char formation is the main failure mechanism in the case of low energyto-thruster-radius ratio. 13 In this paper we present results of microscopic analyses of the charred areas and propose a mechanism of char formation.…”
mentioning
confidence: 99%
“…8,9,13 It was identified that char formation is the main failure mechanism in the case of low energyto-thruster-radius ratio. 13 In this paper we present results of microscopic analyses of the charred areas and propose a mechanism of char formation. To understand this phenomenon, a model of the plasma layer near the Teflon TM surface is developed.…”
mentioning
confidence: 99%